Funcionalidade familiar e sobrevida dos longevos do projeto AMPAL - Rigo, Ilva Inês (2019)
Exceptional length of life is understood as longevity. According to descriptors, the person aged 80 and over is considered to be a long-term person. This is the portion of the population that grows the most, representing in 2010 1.53% of the Brazilian population. By 2050, these individuals will be 6.5%. The longer the life, the greater the chance of developing diseases that compromise autonomy and independence. In situations that compromise these capacities, the family has a role of care, as in other phases of life. It is expected that families with good functionality will act positively on the health conditions of their components. One of the ways to evaluate family functionality is through the "family APGAR " instrument developed in 1978 by Smilkstein. This instrument has a score of 0 to 10, being considered from 0 to 4 high dysfunction, from 5 to 6 moderate dysfunction and from 7 to 10, good family functionality. The present study aims to evaluate if the familiar functionality, observed in the initial interview, influences the survival of the nonagenarians participating in the 2016 Oldest-old Multiprofessional Care Project’s (AMPAL) assessment. The AMPAL identified and evaluated 90 years or older at home in several neighborhoods randomly chosen in Porto Alegre - RS. The situation of death or survival of the participant will be verified through the data published on the website of the Funeral Service Center of Porto Alegre and by telephone contact. In the participants with death, the follow-up time will be calculated by the number of months between the first evaluation and the date of death. Among surviving participants, the follow-up time will be the number of months between the first evaluation and the date of the last contact. Kaplan-Meier Curves and Cox Damage Regression will be used for survival analysis. In the preliminary analyzes, nonagenarians and centenarians with high and moderate family dysfunction were classified as presenting family dysfunction (FD). Of the 228 participants, 73.25% were women. The average female age (92,57 ± 3,70) was higher than the male (P = 0,029), women reported fewer years of schooling (P = 0,031), higher family APGAR scores (9,07 ± 1.75, p = 0,631), higher frequency of widows (p < 0.001), lower MMME score (20,26 ± 6,19; p < 0.001) and higher number of comorbidities (4,72 ± 2,29, p = 0.018). They also came out of the house and participated in social activities with less frequency (P = 0.002 and 0.06). In relation to the activities of daily living, women had poorer basic performance (0 = 0,021) and functional (p < 0.001). The mean APGAR score of the 228 participants of the AMPAL analyzed was 9,05 ± 1,81, the FD frequency was 9.65%. DF was more frequent in men (31.18%; p = 0,572), non-whites (18.18%; p = 0,934), widows (86.36%; p = 0,351), non-illiterate (95.45%; p = 0,311) and residing alone (18.18%, p = 0,634). Among the health conditions, were significantly related to the FD the self-perceived health (P = < 0.001) and the number of depressive symptoms (p < 0.001) and the need for help in administering medications (P = 0,061). This association remained significant in the adjusted analysis. Contact with 14 participants was lost, even after 11 countless attempts. Altogether, 214 participants were successfully followed up, of which 61 (28.5%) passed away. The mean follow-up was 23,22 ± 10,02 months. The surviving participants had lower average age (p < 0.001), Higher MMST score (p < 0.001), reported leaving Home (P = 0.01) and participating in social activities (p < 0.001) more frequently. Survivors had a similar frequency for good family functioning (90% p = 0.994), but more often they were satisfied with their family time (p = 0.032) and with the way the family showed affection and reacted to the feelings (p = 0.083). In the survival analysis, these two components were significantly associated with the lowest injury ratio, even adjusted for age, as well as cognitive performance, social activities and the habit of leaving home. The results allow us to conclude that in addition to the preservation of cognitive performance, to remain physically and socially active, family support is related to the higher survival rate in nonagenarians and centenarians in Brazil.